Building trust, reducing skepticism: Green branding and sustainable purchase behavior in Indonesia - Baharuddin, Sitti Mujahida; Badaruddin, Badaruddin; Fatmasari, Fatmasari; Hafipah, Hafipah (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Growing consumer pressure for businesses to adopt sustainable practices has made green branding a global priority, particularly in emerging markets such as Indonesia where environmental challenges and rising awareness intersect. This study investigates how green brand image and message clarity influence sustainable purchase behavior through the mediating role of consumer trust, and how green skepticism shapes this process. Using a quantitative cross-sectional design, data were collected from 172 Indonesian consumers with prior experience purchasing eco-friendly products. Structural equation modeling with partial least squares (PLS-SEM) was applied to test the hypotheses. The results show that both green brand image and message clarity significantly enhance consumer trust, which in turn strongly drives sustainable purchase behavior. Trust is also confirmed as the key psychological mechanism mediating the effects of brand signals on consumer action. Importantly, the analysis reveals that green skepticism weakens this pathway: even when consumers trust a brand, higher skepticism reduces the extent to which trust translates into sustainable purchases. These findings extend Signaling Theory by demonstrating how trust and skepticism jointly shape consumer responses to green branding in a high-information-asymmetry context. Practically, the study offers actionable insights for managers and policymakers by emphasizing the need for consistent brand identity, transparent communication, and verifiable claims. By addressing both trust-building and skepticism-reduction, businesses can advance more effective green marketing strategies and foster authentic consumer engagement with sustainability.